"It’s a (Kinetic) Trap!" – Selectively Differentiating Allylic Azide Isomers - Topczewski, Joseph J.; Porter, Matthew R. (Synlett, 2018)
Allylic azides are known to undergo the Winstein rearrangement and are often isolated as an equilibrating mixture of isomers. While this process has been known for almost 60 years, very few synthetic applications of this process have been reported. The absence of methods exploiting these intermediates likely stems from a paucity of approaches for gaining the required selectivity to differentiate the isomers. Our lab has made some progress in leveraging this unusual reaction into practical synthetic methodology. Presented herein is a summary of our lab’s recent accomplishments in selectively trapping allylic azides.1 Introduction2 Background: Allylic Azides3 Dynamic Cyclization of Imidates4 Summary and Outlook
Keywords: azides; stereoselective; dynamic kinetic resolution; cyclization; synthesis; allylic